RELATIONSHIP BETWEEN VISUAL PROGNOSIS AND DELAY OF INTRAVITREAL INJECTION OF RANIBIZUMAB WHEN TREATING AGE-RELATED MACULAR DEGENERATION. Issue 7 (July 2015) - Takahashi, Hidenori; Ohkubo, Yuko; Sato, Aya; Takezawa, Mikiko; Fujino, Yujiro; Yanagi, Yasuo; Kawashima, Hidetoshi
Abstract : Background: In age-related macular degeneration, various factors in clinical practice cause delays to arise between the time exudative change is observed and the time anti-vascular endothelial growth factor drugs are actually injected. We investigated the influence of injection delay on prognosis. Methods: Subjects were 50 eyes (50 patients from 2 hospitals) that were administered ranibizumab monotherapy for age-related macular degeneration for 1 year since exudative change was first observed. We investigated the mean number of delay days for each injection. Results: Mean injection delay was between 0 and 104 days. Significant prognostic factors for visual acuity were initial best-corrected visual acuity ( P < 0.01) and mean injection delay ( P = 0.03). We estimated that for an initial best-corrected visual acuity of 0.40 logMAR unit (20/50 Snellen equivalent), the respective best-corrected visual acuity values after 1 year for mean injection delays of 0, 7, 14, 28, and 56 days would be 0.22 (20/33), 0.24 (20/35), 0.26 (20/37), 0.31 (20/40), and 0.39 (20/49). For an initial best-corrected visual acuity of 0.097 (20/25), the respective values would be 0.054 (20/23), 0.075 (20/24), 0.10 (20/25), 0.14 (20/28), and 0.22 (20/33). Conclusion: Long-term visual acuity prognosis worsened when scheduling problems delayed intravitreal injection of anti-vascular endothelial growth factor drugs. Abstract : In age-related macular degeneration, various factors in clinical practice cause delays to arise between the time exudative change is observed and the time anti-vascular endothelial growth factor (VEGF) drugs are actually injected. In this analysis, long-term visual acuity prognosis worsened significantly when scheduling problems delayed intravitreal injection of anti-VEGF drugs.